Bacterial enzyme mediated biosynthesis of gold nanoparticles - Bharde, Atul A.; Kulkarni, Aarohi; Rao, Mala; Prabhune, Asmita; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2007)
Development of synthesis methods for anisotropic metal nanoparticles is of considerable interest due to their remarkable optoelectronic properties. Various shapes ranging from rods to cubes to tetrapods and prisms may be obtained by chemical methods. Here we show that anisotropic gold nanoparticles can be synthesized biologically by the bacterium Actinobacter spp. when challenged with gold chloride in the presence of Bovine serum albumin (BSA). We also observed that synthesis of gold nanoparticles occur with simultaneous induction of the protease enzyme secreted by the bacterium in the presence of BSA. The presence of BSA helps to enhance the rate of gold nanoparticles biosynthesis and may also impart some shape control. Controlling simple experimental conditions like incubation temperature and presence or absence of oxygen have drastic effect on the reaction rate and the morphology of the particles. Various assay experiments show that the presence of enzyme protease can act as a reducing as well as shape directing agent.
Keywords: Biosynthesis; bovine serum; gold nanoparticles